The Theoretical Magnetization Hysteresis Curve of Nd-Fe-B Anisotropic Bonded Magnets - Khanh, Nguyen Van; Vuong, Nguyen Van (Communications in Physics, 2011)
The theoretical magnetization hysteresis curve of Nd-Fe-B anisotropic bonded magnets is simulated using Jiles-Atherton model and random number generation technique. Gaussian statistics was used to assign magnetic particles to random values of magnetic field (H$_{ai}$) and effective interaction ($α )$ parameters. The prospect of anisotropic bonded magnet is evaluated and discussed.